The Indian Ocean - Pearson,Michael (Routledge, 2003)
In this stimulating and authoritative overview, Michael Pearson reverses the traditional angle of maritime history and looks from the sea to its shores - its impact on the land through trade, naval power, travel and scientific exploration. This vast ocean, both connecting and separating nations, has shaped many countries' cultures and ideologies through the movement of goods, people, ideas and religions across the sea.